Նորայայտ հնագոյն կրօնածիսական ինքնահունչ «Ձեռաց զանգ»ը - Կնեազեան, Զաւէն (տպ. Atlas)
The “dzerats zang” is an idiophone for ritual-religious use. It is a small hemispherical metal bell with an average diameter of 10 cm. and a height of 5 cm. We are talking about “discovery” since no specialist in the subject has mentioned them; they are not even mentioned in the lists of traditional instruments, nor among those of ecclesiastical use. The “dzerats zang” is currently widespread among the Armenians of Nor Djugha (Isfahan) and the Peria (Fereydan) region. Analyzing the specimens preserved in museums, we see that they come from places as different as Mush, Vaspuragan, Syunik, etc., which gives us reason to assume that in the recent past the instrument was in use in all regions of historical Armenia and areas of large Armenian population. Over time they fell out of use and survived only among the Armenians of Iran. This instrument is used in the Blessing of Homes ceremonies (Christmas and Easter), and Baptism and Wedding processions. Its use is in force today, but there is a danger that it will be abandoned due to various circumstances.
Keywords: Արուեստ; Կրօնական արարողութիւններ